An uncertain shield: res judicata in arbitration. (1st October 2015) - Ghosh, Varun N.
Abstract : Ending disputes is an important objective of international arbitration. Most arbitration awards are voluntarily respected, so the protection offered by the res judicata doctrine is rarely tested. As a result, the nuances of its application are not always well understood. This article explores the scope of cause of action estoppel, issue estoppel, and the abuse of process doctrine in the context of international arbitration proceedings. The article provides practical guidance in the scope and limits of these principles before UK, Singapore, and Australian courts. Ultimately, the author concludes that practitioners need to be aware of the significant limitations of the res judicata doctrine to accurately evaluate the risk that an arbitral award may not fully determine a dispute.